Nitrogen Losses and Lowland Rice Yield As Affected By Residue Nitrogen Release - Becker, M.; Ladha, J.K.; Ottow, J. C. G. (Wiley, 1994)
Synchronizing N supply from incorporated plant residues with N demand of rice (Oryza sativa L.) may increase the plant's N use efficiency and reduce soil N losses. This hypothesis was tested under flooded lowland conditions in a three‐season field experiment. Leguminous green manures and rice straw with various lignin to N ratios (L/N) and urea were compared using N release, rice N uptake, N use efficiency, grain yield, and total 15N balance as criteria. Basally applied urea resulted in high initial soil NH+4. Where residues were applied, exchangeable NH+4‐N varied as a function of L/N. Daily N uptake by rice peaked at ≈4 wk. Matching of soil NH+4‐N with daily rice N uptake was less apparent in urea and Sesbania rostrata Brem. S. Oberm. treatments than in the S. rostrata‐rice straw mixture treatment. Nitrogen‐15 balances indicated that the mismatch between supply and demand may have caused the measured N losses of 35% from urea and 6 to 10% from S. rostrata applied at 60 kg N ha−1. Synchronized N supply and rice N uptake resulted in negligible N loss and increased the portion of applied N remaining in the soil, but it did not cause a yield increase. Sesbania rostrata‐rice straw mixture depressed yield and N use efficiency in the dry season when yield potential was high. A residual effect was observed in the S. rostrata‐rice straw treatment in the third unfertilized crop, resulting in a 10% increase in grain yield. Apparently, synchronizing soil N supply with N demand by incorporating residues with suitable chemical composition may not immediately increase rice grain yields, but it improves long‐term soil fertility.